2013
DOI: 10.1002/app.39780
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐sorbents from cassava waste biomass and its performance in removal of Pb2+ from aqueous solution

Abstract: Cassava xanthogenate and their derivatives, as adsorbents to remove Pb2+ from aqueous solution, are studied based upon orthogonal factorial design. The structural and thermal properties, adsorption performance as well as equilibrium‐kinetics are comprehensively investigated with multiple tools, such as Fourier transform infrared spectroscopy, thermal gravimetric analysis (TGA), and UV–visible spectrum technique. The influence of multiple parameters, including initial Pb2+ concentrations, compositions, pH value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…There are many well-known processes regarding the treatments of contaminated wastewaters like membrane filtration, 1-4 chemical precipitation, [5][6][7] electrocoagulation, [8][9][10][11][12] reverse osmosis, [13][14][15] adsorbtion, [16][17][18][19][20][21][22][23][24] ion exchange, [25][26][27] etc., all of them with their inherent advantages and disadvantages. At the same time, most of them are not suitable for developing countries due to huge cost investment in terms of use of chemicals, infrastructure, and operation.…”
Section: Introductionmentioning
confidence: 99%
“…There are many well-known processes regarding the treatments of contaminated wastewaters like membrane filtration, 1-4 chemical precipitation, [5][6][7] electrocoagulation, [8][9][10][11][12] reverse osmosis, [13][14][15] adsorbtion, [16][17][18][19][20][21][22][23][24] ion exchange, [25][26][27] etc., all of them with their inherent advantages and disadvantages. At the same time, most of them are not suitable for developing countries due to huge cost investment in terms of use of chemicals, infrastructure, and operation.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is extremely important to find efficient methods to mitigate the side effects of the pretreatments that favor an increased adsorption capacity. Other studies involving the removal of metal ions and anions from aqueous solution can be found in Table and Table . As well as the synthesis parameters and reaction conditions are mentioned in Table .…”
Section: Development Of New Adsorbents From Lignocellulosic Residuesmentioning
confidence: 99%
“…In the literature, various parts of cassava are reported to be adsorbents used in the removal of heavy metals, for example, zinc ( [10][11][12][13]), copper ([11, 13-21]), lead ( [20][21][22][23][24][25][26][27][28]), cobalt ( [29,30]), vanadium [30], chromium ([13, 17, 30, 31]), and cadmium ( [12,15,[32][33][34]), dyes such as rhodamine B [35], direct red [36], methylene blue ( [36][37][38][39][40]), methyl orange [40], and reactive dyes [41], antibiotics ([22, 42-44]), phosphorous [45], biodiesel purifcation [46], organic pollutants from industrial efuents ( [29,47,48]), and free fatty acid [49]. In addition, ZnO nanoparticles synthesized from cassava starch are used as adsorbents [50].…”
Section: Introductionmentioning
confidence: 99%